Trajetórias negligenciadas: processos de resiliência em adolescentes com histórico de envolvimneto no tráfico de drogas - Pessoa, Alex Sandro Gomes [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This research was conducted in the Graduate Program on Education located at Universidade Estadual Paulista (UNESP, Presidente Prudente campus - SP) and was associated to themes on Formative Processes, difference and values. The main objective of this study was to analyze the trajectories of adolescents involved in drug trafficking from the point of view of their developmental contexts, as well as understand mechanisms associated to resilience processes. The survey included 565 adolescents between 12-20 years old (M = 16,01; SD = 1,548), both genders (56,3% male) who were attending four institutional contexts which offer diversified services. Through criteria previously established, a group of adolescents with history of involvement in drug trafficking was formed and it allowed the conduction of quantitative and qualitative analysis, in alignment with the mixed-method studies approach. Therefore, two quantitative instruments were used: 1) IRPPAR (Protective Factor in the Adolescence Associated to Resilience), in order to evaluate the protective contexts and institutions in their lives; 2) CYRM (Child and Youth Resilience Measure), which brought indicative of resilience processes in the populations studied. After conducting statistical procedures, a new group of adolescents (n = 8) with high level of involvement in drug trafficking and positive indicators associated to resilience was formed, which allowed to conduct semi-structured interviews...

Essa pesquisa foi realizada junto ao Programa de Pós Graduação em Educação da Universidade Estadual Paulista (UNESP, campus de Presidente Prudente - SP) e esteve vinculada à linha de pesquisa intitulada Processos Formativos, diferença e valores. O objetivo central desse estudo foi analisar as trajetórias de vida de adolescentes com envolvimento no tráfico de drogas a partir do desvelamento de seus contextos de desenvolvimento, bem como compreender processos que estão associados à resiliência. Participaram desse estudo 565 adolescentes, entre 12-20 anos de idade, (M = 16,01; DP = 1,548), de ambos os sexos (56,3% do sexo masculino) e que recebiam atendimentos em quatro contextos institucionais que oferecem serviços diversificados. Por intermédio de alguns critérios de inclusão estabelecidos previamente, um grupo de adolescentes com envolvimento no tráfico de drogas foi formado e possibilitou que análises quantitativas e qualitativas fossem realizadas, em alinhamento com a abordagem mixedmethod studies. Desse modo, foram aplicados dois instrumentos quantitativos: 1) IRPPAR (Indicadores de Proteção na Adolescência Associados á Resiliência), com o objetivo de averiguar os contextos de proteção; 2) CYRM (Child and Youth Resilience Measure), que trouxe indicativos de processos de resiliência nas populações estudadas. Após a realização de procedimentos estatísticos, um grupo de adolescentes (n = 8) com alto nível de envolvimento no tráfico e com indicadores positivos de resiliência foi formado...
Keywords: Educação; Adolescência; Resiliencia (Traço da personalidade); Risco - Aspectos sociologicos; Trafico de drogas; Proteção; Education